A one‐dimensional cobalt(II) coordination polymer based on 2, 4′‐oxydibenzoic acid: poly[[[diaquabis[2‐(4‐carboxyphenoxy)benzoato‐κO1]cobalt(II)]‐μ‐4, 4′‐bipyridine‐κ2N:N′] dihydrate]. Issue 7 (5th June 2014) - Tang, Long; Fu, Feng; Wang, Ji‐Jiang; Liu, Qi‐Rui; Zhao, Hang‐Hang
<x xml:space="preserve">Abstract</x> The reaction of CoSO4 with 2, 4‐oxydibenzoic acid (H2oba) and 4, 4′‐bipyridine (bipy) under hydrothermal condition yielded a new one‐dimensional cobalt(II) coordination polymer, [Co(C14H9O5)2(C10H8N2)(H2O)2]·2H2On, which was characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis, magnetic properties and single‐crystal X‐ray diffraction. The CoII ions are connected by bipy ligands into infinite one‐dimensional chains. The Hoba− ligands extend out from the two sides of the one‐dimensional chain. O—H...O hydrogen bonding extends these chains into a two‐dimensional supramolecular architecture.